2022
DOI: 10.3390/vetsci9030116
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Responses and Ex Vivo IFN-γ Production after Canine Whole Blood Stimulation with Leishmania infantum Antigen or KMP11 Recombinant Protein

Abstract: The effect of Leishmania infantum soluble antigen (LSA) and recombinant Kinetoplastid Membrane Protein 11 (rKMP11) on the induction of ex vivo specific IFN-γ (n = 69) and antibody responses (n = 108) was determined in dogs. All dogs were tested for serological response to both antigens and divided into Group 1: healthy (Asturias, Spain, n = 26), Group 2: sick (n = 46), Group 3: healthy Ibizan hounds (Mallorca, Spain, n = 22) and Group 4: healthy (Bari, Italy, n = 14). Antibody levels were higher for LSA when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Aslan et al [ 34 ] found that IL-2 expression was negatively correlated with splenic parasite loads in experimentally infected dogs [ 31 ]. Our results are in agreement with previous data, indicating a natural resistance against leishmaniosis in Ibizan Hounds compared to other canine breeds [ 11 , 24 , 32 ]. The gene encoding for IL-2 is located at chromosome 19 and presents four exons.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Aslan et al [ 34 ] found that IL-2 expression was negatively correlated with splenic parasite loads in experimentally infected dogs [ 31 ]. Our results are in agreement with previous data, indicating a natural resistance against leishmaniosis in Ibizan Hounds compared to other canine breeds [ 11 , 24 , 32 ]. The gene encoding for IL-2 is located at chromosome 19 and presents four exons.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the upregulation of IFN-γ has been correlated with low disease severity [ 23 ]. Furthermore, stimulation with Leishmania infantum soluble antigen (LSA) in Ibizan Hound dogs provokes higher IFN-γ serum levels than in other healthy or sick dog breed [ 24 ]. The IFNG gene is located at chromosome 10 and presents four exons that codify a unique protein with 166 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Aslan et al (2016) found that IL-2 expression was negatively correlated with splenic parasite loads in experimentally infected dogs [37]. Our results are in agree with several authors, which suggest a natural resistance in Ibizan hound against leishmaniosis compared to other canine breeds [23,38,39]. The gene encodes for IL-2 is located at chromosome 19 and presents four exons.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, this upregulation of IFN-γ has been correlated with low severity of disease [28]. Furthermore, stimulation with Leishmania infantum soluble antigen (LSA) in Ibizan hound dogs provokes a higher IFN-γ serum levels than in other healthy or sick dogs breed [29]. The IFNG gene is located at chromosome 10 and presents four exons that codify a unique protein with 166 aminoacids.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-18, known as IFN-γ inducing factor, increases the production of this interferon by T cells and has a relevant role in the defense against visceral leishmaniasis [42,43]. According to that, these three cytokines (IFN-γ, IL-2 and IL-18) present high levels in Ibizan Hound dogs, which have a natural resistance against canine leishmaniasis [39,[44][45][46]. Our results indicate that these elevated levels are correlated with IL6-CGAAG haplotype which is found with a higher frequency in the Ibizan Hound dogs compared to Boxer ones.…”
Section: Discussionmentioning
confidence: 99%